Between ‘Āriyah and Gaṣb: Legal Ambiguity in The Unauthorised Use of Property in Islamic and Positive Law - Abd Aziz Tambunan; Ahmad Mafaid (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2026)
The widespread practice of using others’ property without explicit permission in communal settings raises a significant legal ambiguity regarding its classification between ‘āriyah (gratuitous loan) and gaṣb (unlawful appropriation). This ambiguity becomes critical as such practices are socially normalized, yet potentially generate disputes over rights, liability, and ownership. This study aims to analyse the legal status of unauthorised use of property by clarifying the boundary between ‘āriyah and gaṣb, and examining its implications within Islamic law and positive law. This research employs a qualitative normative-analytical approach, drawing on doctrinal analysis and observation of everyday practices in public and semi-public environments. The findings demonstrate that the absence of explicit consent shifts the legal character of use from permissible ‘āriyah toward gaṣb, thereby triggering liability (ḍamān) under Islamic law. In contrast, positive law tends to frame such conduct within the scope of unlawful acts or, under certain conditions, elements of theft. The study’s contribution lies in clarifying the often-overlooked boundary between socially tolerated practices and legally prohibited acts, highlighting a gap between normative legal principles and lived practices. This gap underscores the need for clearer consent-based norms, institutional regulation of shared property, and legal awareness to prevent disputes and ensure accountability.